Severity of radiographic changes in patients with COVID-19 pneumonia - experience from secondary-level hospital - Pavić Aleksandra; Janković Ivan; Novković Aleksa (Srpski Arhiv za Celokupno Lekarstvo)
Introduction/Objective. Chest X-ray (CXR) is a common diagnostic procedure for monitoring the course and outcome of pneumonia. The aim of the study was to examine the frequency, type and degree of CXR changes in COVID-19 pneumonia and compare it with demographic data and the presence of comorbidities. Methods. In this retrospective study, CXRs taken on the day of admission were analyzed for 620 patients with COVID-19. CXR were defined as ground-glass opacification (GGO), consolidation, reticular changes, pulmonary nodules, and pleural effusions. CXR severity score (CXR-SS) was determined based on the adjusted Radiographic Assessment of Lung Edema score. SPSS version 17.0 was used for statistical analyses. Results. The average age was 62.75 ± 14.8 years 66.5% of analyzed patients had comorbidities. CXR changes were bilateral in 53.2%, dominant in the lower lung in 68.1% and diffuse in 24.5%. GGO were present in 55%, reticular changes in 37.3%, and consolidations in 24% of patients. Based on CXR-SS, 47.2% of patients had mild pneumonia, 40.2% moderate, 7.9% severe, and 4.6% very severe. Severe/very severe pneumonia was in 71.8% of older than 65 years. Bilateral changes were found in 97.4% of people with severe/very severe pneumonia, diffuse in 56.4%, and consolidation in 66.7% of the patients. GGO were in 58.1% of subjects with mild/moderate pneumonia. Conclusion. CXR in patients with COVID-19 pneumonia are more frequently bilateral, dominantly peripheral, in the lower lung zone. The degree of diffuse changes is proportional to older age and more frequent comorbidities. In a severe form of the disease, consolidation and reticular opacification dominate.